Sero-Surveillance to assess immunity to rubella and assessment of immunogenicity and safety of a single dose of rubella vaccine in school girls - Sharma Hitt; Chowdhari Sunil; Raina Tilak; Bhardwaj Subodh; Namjoshi Gajanan; Parekh Sameer (Wolters Kluwer Medknow Publications, 2010)
Background: Rubella vaccination is not yet included in National Immunization Schedule in India. Serosurvey is frequently used to assess epidemiologic pattern of Rubella in a community. Serosurveys in different parts of India have found that 6-47% of women are susceptible for Rubella infection. The present serosurveillance was conducted in Jammu, India, in two public schools. Objective: To determine serological status of Rubella antibodies of school girls and assessment of immunogenicity and reactogenicity of Rubella immunization in seronegative girls. Materials and Methods: The current study was conducted to determine Rubella serostatus in peripubertal schoolgirls aged 11-18 years and also to assess immunogenicity and safety of Rubella vaccine (R-Vac) of Serum Institute of India Ltd., Pune, in seronegative girls. For screening, pre-vaccination serum Rubella IgG antibodies were determined and to assess immunogenicity of the vaccine, post-vaccination IgG antibodies were compared with pre-vaccination levels. Safety assessment was done for a period of 8 weeks, post-vaccination. Results: A total of 90 (32.7%) seronegative girls were vaccinated. All girls (100%) became seropositive, post-vaccination. Clinically relevant and statistically significant increase in anti-Rubella IgG titres was observed. The adverse events were mild and self-limiting. Conclusions: R-Vac vaccine used in the study demonstrated an excellent safety and immunogenicity profile.